2001
DOI: 10.1191/096120301678416015
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIa/IIIa polymorphism and its association with clinical manifestations in Korean lupus patients

Abstract: The aim of this study was to determine the distribution of the FcgammaRlla and FcgammaRIIIa polymorphisms and their association with clinical manifestations in Korean lupus patients. Three hundred SLE (systemic lupus erythematosus) patients (48 male, 252 female) meeting 1982 ACR criteria and 197 Korean disease-free controls were enrolled. Genotyping for FcgammaRlla 131 R/H and FcgammaRIIIa 176 F/V was performed by PCR of genomic DNA using allele-specific primers and the FcgammaRIIIa genotype was confirmed by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…45 Yun et al described an earlier occurrence of photosensitivity and oral ulcers in Korean patients with the IIA-R/R131 genotype, which is in accordance with our findings. 46 This trend was also found for patients with the genotype FcγRIIIA-F/F158 (earlier occurrence of symptoms: p<0.05 in 22% of the tested variables; higher frequency: p<0.05 in 12.5% of the tested variables) and FcγRIIIB-NA2/2 (p<0.05 in 9% and 5% respectively). In the double negative genotypes we observed an accumulation of effects with even higher incidence and earlier onset of various symptoms (earlier occurrence of symptoms: p<0.05% in 42% of the tested variables; higher incidence: p<0.05 in 14%).…”
Section: Discussionmentioning
confidence: 55%
“…45 Yun et al described an earlier occurrence of photosensitivity and oral ulcers in Korean patients with the IIA-R/R131 genotype, which is in accordance with our findings. 46 This trend was also found for patients with the genotype FcγRIIIA-F/F158 (earlier occurrence of symptoms: p<0.05 in 22% of the tested variables; higher frequency: p<0.05 in 12.5% of the tested variables) and FcγRIIIB-NA2/2 (p<0.05 in 9% and 5% respectively). In the double negative genotypes we observed an accumulation of effects with even higher incidence and earlier onset of various symptoms (earlier occurrence of symptoms: p<0.05% in 42% of the tested variables; higher incidence: p<0.05 in 14%).…”
Section: Discussionmentioning
confidence: 55%
“…Yun et al (2001) identified that FCGRIIA R131 homozygote was a major predisposing factor for SLE and LN, and H131/V176 was a protective allele combination in LN. However, FCGRIIA was not associated with Chinese (Yap et al 1999) and Japanese SLE (Hatta et al 1999;Sato et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Association of FcγR genes with various diseases in Korean populations have been previously reported, such as (Song et al 1998;Yun et al 2001;Lee et al 2002;Lee et al 2003), adult onset Still's disease (FCGRIIA H/R131, FCGRIIIA F/ V176, and FCGRIIIB NA1/NA2) (Oh et al 2002;Woo et al 2009), and ischemic stroke (FCGRIIA rs7511868, rs6427595, rs7512140, and rs6696854) (Kim et al 2009b). …”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in African-American, Brazilian, German, and Thai populations have found significant associations between the FcγRIIA 131R allele and SLE disease susceptibility or severity of nephritis [71,126,128,129,131,133,136,137,144]. Moreover, several studies in Caucasian, Dutch, and Korean populations have found associations between the FcγRIIIA 158F allele and disease susceptibility and severity [127,130,134,145].…”
Section: The Activating Fcrs In the Efferent Responsementioning
confidence: 94%
“…In the majority of studies, however, the low-affinity alleles have been identified as risk factors for the development or severity of autoimmune disease. Several studies have found an association of the low-affinity FcγRIIIA 158F and the FcγRIIA 131R alleles with the incidence and severity of lupus nephritis and arthritis [71,[125][126][127][128][129][130][131][132][133][134][135][136][137]. In addition, the low-affinity allele of human FcγRIIIB (FcγRIIIB-NA2) has been associated with SLE [71,138,139].…”
Section: The Activating Fcrs In the Efferent Responsementioning
confidence: 99%